FLOW ANALYSIS OF OVERTAKING VEIDCLES: CFD STUDY - Mohamed Saad, Ahmed (Universiti Teknologi PETRONAS, 2010)
The aerodynamic forces occurring when one road vehicle overtakes another are to be investigated using two-dimensional (2D) computational fluid dynamics. Although a lot of researches have been carried on the aerodynamics of the flow of overtaking vehicles, very little information is available on flow around full scale vehicles. Increasing the size of models I 0 times would results in the increase of the mesh size, making it more expensive and requires higher performance hardware. This research studied the aerodynamic forces by the quasi static approach using CFD analysis; it also laid the grounds for further transient and 3D investigation on the full scale model and discussed their feasibility. The purpose of this report is to discuss the outcomes of my final year project with some guidance on how to reach these results for further investigations.